'The wonderful world of Ohio': Paternalism and the unifying logic of dependency in American political development - Coccia, A (2020)
This thesis examines the evolution of conservative ideas about U.S. welfare reform, demonstrating the primacy of the new paternalism in a case study of Ohio.